Remittances, Livelihood Strategies, and Family Resilience of Retired Indonesian Migrant Workers: a Case Study of Kenanga Village, Indramayu - Susilawati, Etic; Wahyuni, Ekawati Sri; Kolopaking, Lala M (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2026)
Indonesian retired female migrant workers (RFMWs) are pivotal in strengthening household economic and social resilience post-migration. This study analyzes remittance management, livelihood strategies, and family resilience among RFMWs in Kenanga Village, Indramayu Regency. A mixed-methods approach was applied, combining a survey of 80 households with in-depth interviews. Research instruments included a livelihood strategy questionnaire and the Walsh Family Resilience Questionnaire (WFRQ). Results show that remittances were primarily used for housing construction or renovation, children's education, and business capital, enhancing physical and financial assets. The dominant livelihood strategy was non-agricultural business diversification due to limited natural capital. As many as 83.75% of households had high resilience, characterized by open communication, role flexibility, and adaptive capacity. These findings highlight the need for integrating remittance management with livelihood strategies to reinforce post-migration family resilience. Remittance management functions as an economic resource that supports household livelihood strategies, while livelihood strategies determine the sustainable use of remittances. These two dimensions are mutually reinforcing and, when integrated, contribute significantly to strengthening post-migration family resilience.